Efektifitas Komsumsi Tablet Fe dengan Air Jeruk Nipis terhadap Peningkatan Kadar HB Ibu Hamil Anemia Ringan Trimester III - Wanda Wanda; Margiyati Margiyati; Eka Oktavia (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Anemia is a body condition where the hemoglobin level in red blood cells is lower than the normal standard. Pregnant women are said to be anemic if their Hb content is <11gr/dL. According to WHO, the prevalence of pregnant women throughout the world who experience anemia is 41.8%. The percentage of anemia in pregnant women in Indonesia is 37.1%. For the Special Region of Yogyakarta, the prevalence in pregnant women is 19.01%, and the highest incidence of anemia is in Bantul Regency (27.67%). Data from the Bantul District Health Service, from 27 Community Health Centers, there are 5 Community Health Centers with the highest number of anemia, namely at Sewon II Community Health Center. From this data, Sewon II Community Health Center is in second place. Objective: To determine the effectiveness of consuming fe tablets with lime juice on increasing Hb levels in mildly anemic pregnant women at the Sewon II Bantul Community Health Center, Yogyakarta. Method: This quasi-experiment research uses a one group pretest-posttest design. The sample in the study consisted of 30 pregnant women. The sampling technique uses total sampling. The research instrument gave lime to pregnant women with mild anemia for 2 weeks. Then the hemoglobin level was checked before and after drinking lime using a hemoglobin meter checking device in collaboration with the Puskesmas lab section. Results: The results of this research are based on univariate analysis of the characteristics of respondents aged 20-35 years as many as 26 (86.3%) respondents, the majority have a high school education as many as 26 (86.7%) respondents, the occupation of respondents is housewives 28 (93.3%) ) respondents. The results of the bivariate analysis showed that there was a significant effect on the average value of increasing hemoglobin levels before (10.21) and after drinking lime (11.23) with an average of (1.02). Conclusion: Based on the research results, it can be concluded that there is an effect of giving lime juice on hemoglobin levels in pregnant women in the second trimester at the Sewon II Bantul Community Health Center.